Odpowiedź :
[tex]Aby\ dodac\ lub\ odjac\ ulamki,\ nalezy\ sprowadzic\ je\ do\ wspolnego\ mianownika .\\\\a)\\\\-\frac{3}{4}+(-8\frac{5}{8})+(-6\frac{5}{6}) +(-1\frac{3}{8})= -\frac{3}{4} -8\frac{5}{8} -6\frac{5}{6} -1\frac{3}{8} = -\frac{18}{24} -8\frac{15}{24} -6\frac{20}{24} -1\frac{9}{24} =\\\\= -15\frac{62}{24}=-17\frac{14}{24}=-17\frac{7}{12}[/tex]
[tex]b)\\\\-14\frac{1}{2}+(-7\frac{3}{5})+8\frac{1}{5}+(-6,3)=-14\frac{1}{2} -7\frac{3}{5} +8\frac{1}{5} -6 \frac{3}{10}=\\\\=-14\frac{5}{10} -7\frac{6}{10} +8\frac{2}{10} -6 \frac{3}{10}=-21\frac{11}{10} +8\frac{2}{10} -6 \frac{3}{10}=-13\frac{9}{10}-6\frac{3}{10}=\\\\=-19\frac{12}{10}=-20\frac{2}{10}=-20\frac{1}{5}[/tex]
[tex]c)\\\\20+(-16,3)+4\frac{1}{3}+(-18\frac{2}{3})=20 -16\frac{3}{10} +4\frac{1}{3} -18\frac{2}{3} =20 -16\frac{9}{30} +4\frac{10}{30} -18\frac{20}{30} =\\\\=3\frac{21}{30} +4\frac{10}{30} -18\frac{20}{30} = 7\frac{31}{30}-18\frac{20}{30} = 8\frac{ 1}{30}-18\frac{20}{30}=-10\frac{19}{30}[/tex]
[tex]d)\\\\ -0,6+2\frac{3}{8}+(-7\frac{5}{8})+(-\frac{1}{2})+0=- \frac{6}{10}+2\frac{3}{8} -7\frac{5}{8} -\frac{1}{2}=- \frac{24}{40}+2\frac{15}{40} -7\frac{25}{40} -\frac{20}{40}=\\\\=- \frac{24}{40}+1\frac{55}{40} -7\frac{25}{40} -\frac{20}{40}=1\frac{31}{40} -6\frac{65}{40} -\frac{20}{40}=-5\frac{34}{40}-\frac{20}{40}=-5\frac{54}{40}=\\\\=-6\frac{14}{40}=-6\frac{7}{20}[/tex]